Cationic phosphorus dendron nanomicelles deliver microRNA mimics and microRNA inhibitors for enhanced anti-inflammatory therapy of acute lung injury. (6th January 2023) - Li, Jin; Chen, Liang; Sun, Huxiao; Zhan, Mengsi; Laurent, Regis; Mignani, Serge; Majoral, Jean-Pierre; Shen, Mingwu; Shi, Xiangyang
Abstract : Cationic phosphorus dendron micelles can be developed to co-deliver microRNA mimics and microRNA inhibitors for acute lung injury gene therapy. Abstract : The development of efficient nanomedicines to repress the repolarization of M1 phenotype macrophages and therefore inhibit pro-inflammatory cytokine overexpression for anti-inflammatory therapy is still a challenging task. We report here an original gene delivery nanoplatform based on pyrrolidinium-modified amphiphilic generation 1 phosphorus dendron (C12G1) nanomicelles with a rigid phosphorous dendron structure. The nanomicelles display higher gene delivery efficiency than the counterpart materials of pyrrolidinium-modified G1 phosphorus dendrimers, and meanwhile exhibit excellent cytocompatibility. The C12G1 nanomicelles can be employed to co-deliver the miRNA-146a mimic (miR-146a mimic) and miRNA-429 inhibitor (miR-429i) to inhibit the Toll-like receptor-4 signaling pathway and p38 mitogen-activated protein kinase signaling pathway, respectively, thus causing repression of M1 phenotype alveolar macrophage polarization. The developed C12G1/miR-mixture polyplexes enable efficient therapy of lipopolysaccharide-activated alveolar macrophages in vitro and an acute lung injury mouse model in vivo . The generated cationic phosphorus dendron nanomicelles may hold promising potential for anti-inflammatory gene therapy of other inflammatory diseases.